Students' motivation towards the involvement in co-curricular activities in school / Roy Hendra Mohd Fauzi - Mohd Fauzi, Roy Hendra (2014)
This research was conducted to identify the students' motivation towards involvement in co-curricular activities in school. The aims of the study were to determine the motivation factors to involve in co-curricular activities, the barriers that facing by the students to involve in the activity and also the effectiveness of co-curricular activity for the students. Nowadays, many school students are not taking serious about the co-curricular involvement and they feel the co-curricular is not important. They just only focus to their academic achievement without give the same commitment towards cocurricular involvement. Thus, this study demonstrate why it is important to the students to participate in co-curricular activity to prevent and if can to reduce the absenteeism among students during co-curriculum period. The respondents for this study were 105 students from SMK Seksyen 9, Shah Alam, Selangor that consist of form one, two and four students. They were randomly chosen as the respondents through simple random sampling. The data was then analyzed by using Statistical Package of Social Science to find the mean, frequency, and standard deviation by using descriptive statistics and one way ANOVA. The findings show that the motivation of the students came from several factors such as parents, teachers, family and peers and personal factors. It divided into intrinsic and extrinsic motivation. Meanwhile, there are three types of truancy that are class truancy, school truancy and co-curriculum truancy. This study also indicates that the barriers that cause the students not involve in co-curricular activity. The finding also reveals the effectiveness of co-curricular activities for the students and the respondents also believe with the effectiveness of co-curriculum